Design of La2−xPrxNiO4+δ SOFC cathodes: a compromise between electrochemical performance and thermodynamic stability. Issue 3 (20th December 2016) - Sharma, Rakesh K.; Cheah, Seng-Kian; Burriel, Mónica; Dessemond, Laurent; Bassat, Jean-Marc; Djurado, Elisabeth
Abstract : A novel architecturally designed LaPrNiO4+ δ IT-SOFC cathode shows the best compromise between thermodynamic stability and electrochemical properties. Abstract : Architecturally designed La2− x Pr x NiO4+ δ (with x = 0, 0.5, 1 and 2) cathodes on the Ce0.9 Gd0.1 O2− δ (CGO) electrolyte have been prepared with a view to take advantage of the complimentary properties of the two extreme compositions La2 NiO4+ δ and Pr2 NiO4+ δ, i.e. the superior stability of La2 NiO4+ δ and the higher electronic conductivity of Pr2 NiO4+ δ . The design consists of stacking of two layers starting with a 3D tree-like microstructure (∼20 μm thick) over a thin dense base layer (∼100 nm) fabricated in one step by electrostatic spray deposition (ESD) and then topped by using a screen-printed (SP) current collecting layer of the same composition. X-ray diffraction confirms the formation of a complete solid solution crystallizing in a single phase orthorhombic structure with the Fmmm space group. The thermodynamic stability and polarisation resistance ( R pol ) decrease by increasing the Pr content. Among the complete La2− x Pr x NiO4+ δ solid solutions, LaPrNiO4+ δ shows the best compromise between electrochemical properties (the lowest R pol value available in the literature for this composition, 0.12 Ω cm 2 at 600 °C) and thermodynamic stability in air. Moreover, an anode supported single cell (Ni-3YSZ/Ni-8YSZ/8YSZ/CGO) including the LaPrNiO4+ δ double layer electrode shows a maximum power density of 438 mW cm −2 at 700 °C.